Doxycycline In Pityriasis Rosea: Placebo- Controlled Clinical Trial - Al-Timimi, Ghassaq; Al-Mashhadani, Sabeeh; Al-Waiz, Makram (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Pityriasis rosea is an acute, self-limiting skin disease, probably of infective origin. Doxycycline is a broad-spectrum antibiotic, and most probably has animmunomodulator and an anti-inflammatory effect.Objective: To assess the efficacy of doxycycline in the treatment of pityriasis rosea in patients evaluated between January 2001 and May 2002.Patients and methods: This was a placebo-controlled clinical trial. One hundred and twenty patients with pityriasis rosea were included in the study; all of them were above 12 years ofage. They had been divided into 2 groups, the treatment group consisted of 60 patients and received doxycycline capsule. 100,mg orally for 14 days and the placebo group consisted of60 patients and received glucose capsules for 14 days, all the patients were followed up clinically for 4 weeks after treatment, the responses were categorized into excellent, partialand no response.Results: forty-six patients from the treatment group completed the study. Excellent response was achieved in 30 patients (65%), partial response in 15 patients (33.5%) andno response in I patient (1.5%). Forty patients from the placebo group completed the study. Excellent response was achieved in 4 patients (10%), partial response in 20 (50%)and no response in 16 patients (40%). The results were statistically significant.Conclusions: we concluded that doxycycline was effective in the treatment of pityriasis rosea, with very few adverse effects.